1993
DOI: 10.1111/j.1749-6632.1993.tb26255.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic Targets of HIV Infection: T Cellsa

Abstract: One of the principal targets of HIV infection is the human peripheral blood CD4+ T cell, resulting in progressive CD4+ lymphocyte loss. Hypothesized mechanisms for this loss include apoptosis, cytolytic reactions, V-beta gene deletion of the T-cell receptor (TCR) by superantigens, CD4+ lymphocyte syncytium formation, and autoimmune reactions. In adults with HIV infection, the critical decline in CD4+ lymphocyte number that heralds the onset of AIDS-defining conditions is well characterized, whereas in infants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Diminution of CD4 + T-cells and haematological complications are hallmarks of HIV disease progression [15] associated with increase morbidity and mortality [16]. The incidence and severity of these factors generally correlate with the stage of the disease with anaemia being the most common and important haematologic predictor of HIV progression to AIDS [17].…”
Section: Discussionmentioning
confidence: 99%
“…Diminution of CD4 + T-cells and haematological complications are hallmarks of HIV disease progression [15] associated with increase morbidity and mortality [16]. The incidence and severity of these factors generally correlate with the stage of the disease with anaemia being the most common and important haematologic predictor of HIV progression to AIDS [17].…”
Section: Discussionmentioning
confidence: 99%
“…[1,2] Depletion of CD4ϩ T cells is one of the hallmarks of progression of HIV infections. [3] The absolute CD4 cell count is used routinely in the evaluation and monitoring of HIV-infected persons. [4] CD4 cell counts have been found to have good correlation with development of various complications in HIV/AIDS.…”
Section: Introductionmentioning
confidence: 99%
“…A preliminary report of the immune function of the children enrolled in the National Institutes of Health National Heart, Lung and Blood Institute P 2 C 2 HIV‐1 Study recorded the measurements of CD4 + (helper) T cells and CD8 + (cytotoxic) T cells in HIV‐1 + children followed for less than 24 months of the 60‐month study. 1 Results of this study showed an early and continuing loss of CD4 + T cells through 17 months of age in HIV‐1 + children and an early rise at 2‐4 months followed by a decline of CD4 + T cells in HIV‐1 − children, although at 17 months the mean cell count was higher by 1,200 cells/μl. There was an expansion of the CD8 + T‐cell population, beginning as early as 2 months of age in some HIV‐1‐infected children and rising to 50% of the peripheral blood mononuclear cell population.…”
Section: Introductionmentioning
confidence: 61%